A metatheory explaining how patients manage tooth loss. (15th April 2020) - Al‐Sahan, Maha M.; MacEntee, Michael I.; Bryant, S. Ross
Abstract: Objectives: To explore how a metatheory composed of five dominant psychosocial theories of communication, developmental regulation, emotions, resources and social cognition, explains the beliefs, concerns and experiences, of people experiencing tooth loss. Background: Complete tooth loss is the leading cause of disability associated with oral conditions in 19 of 21 global regions, and it is among the most difficult treatment challenges in dentistry. Methods: Interviews with 18 participants were analysed inductively using interpretive description and qualitative synthesis to explain their beliefs and experiences relating to tooth loss. Results: Theoretical constructs from the five dominant theories constituting the metatheory explained the beliefs, concerns and experiences of the participants. For example, both before and after tooth loss they engaged in adaptive behaviours according to developmental regulation theory; implemented management strategies according to emotion theory, social cognitive theory, and resource theory; sought help from friends and dental professionals according to communication theory; and modified their physical and social activities according to social cognitive theory. Conclusion: A metatheory synthesised from five dominant theories addressing communication, personal background, emotions, resources and social awareness, offers a comprehensive and plausible explanation of how people respond psychologically and socially to the loss of their teeth, and expands the scope of information needed to help manage their loss and subsequent treatment.